Keplerate-type polyoxometalate Mo72Fe30 nanoparticle anodes for high-energy lithium-ion batteries. Issue 41 (21st September 2020) - Huang, Shao-Chu; Lin, Chia-Ching; Hsu, Chi-Ting; Guo, Chun-Han; Chen, Tsan-Yao; Liao, Yen-Fa; Chen, Han-Yi
Abstract : Mo72 Fe30 as an anode for lithium-ion batteries with a capacity of 1250 mA h g −1, 92% retention up to the 100 th cycle, an excellent rate performance (868 mA h g −1 at 2 A g −1 ), and a high energy density of 258 W h kg −1 was studied by in operando measurements. Abstract : Li-ion batteries (LIBs), with high energy densities, have been explored in recent years. Polyoxometalates (POMs) have been proposed as promising anodes, with high capacity. Herein, we report a Keplerate-type POM [Mo6 O19 ⊂{Mo72 Fe30 O254 (CH3 COO)12 (H2 O)96 }]·150H2 O (Mo72 Fe30 ) nanoparticle as a high energy anode material for LIBs for the first time. Employing synchrotron radiation X-rays, we conducted in operando and ex situ measurements to investigate the charge storage mechanisms of Mo72 Fe30 . The in operando X-ray absorption near edge structure (XANES) reveals that a single Mo72 Fe30 molecule can store 377 electrons. The Mo72 Fe30 anode exhibits a high capacity of ∼1250 mA h g −1 at 100 mA g −1, with 92% capacity retention after 100 cycles, and it also demonstrates an excellent rate performance (868 mA h g −1 at 2000 mA g −1 ). Li-ions can react with Mo72 Fe30 through surface-capacitive reactions and diffusion processes, and the Li-ion diffusion coefficient of Mo72 Fe30 is up to 10 −10 cm 2 s −1, resulting in high rate performance. Furthermore, a full-cell utilizing Mo72 Fe30 as an anode and LiFePO4 as a cathode was assembled, and it delivered a high energy density of 258 W h kg −1, which successfully demonstrates that Mo72 Fe30 is a promising anode material for LIB applications.